Triangular ideal relative convergence on modular spaces and Korovkin theorems - ÇINAR, Selin; YILDIZ, Sevda (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
In this paper, we introduce the concept of triangular ideal relative convergence for double sequences of functions defined on a modular space. Based upon this new convergence method, we prove Korovkin theorems. Then, we construct an example such that our new approximation results work. Finally, we discuss the reduced results which are obtained by special choices. Mathematics Subject Classification (2010): 40A35, 41A36, 46E30. Received 23 February 2021; Accepted 22 April 2021. Published Online: 2023-12-11 Published Print: 2023-12-30